A thermal improvement technique for phase windings of electrical machines - Galea, Michael; Gerada, C.; Raminosa, Tsarafidy; Wheeler, Patrick (IEEE, 2012)
In electrical machines, a higher torque/force density can usually be achieved by increasing the current density in the windings. However, the resulting increase in copper losses leads to higher temperatures in the coils, especially in the centre of the slots where the thermal resistance to the ambient/cooling surfaces is highest. In this paper a novel, simple technique is presented in which a higher thermal conductivity path between the centre of the slot and the cooling arrangement is created, thus increasing the heat flow away from the slot centre. A lumped parameter thermal model is presented and used along with finite element analysis to investigate the effectiveness of the proposed technique. The lumped parameter model is also used for optimizing the high conductivity path for maximum air-gap shear stress and to obtain a compromise between the reduced slot area and the improved temperature distribution. Experimental validation is then presented to compare the predicted results with the measured results on a purposely built instrumented set-up.